Effect of Low-Dose Bisphosphonates on Fracture Healing in Patients with Pathological Bone Fractures - Alkhatteib, Hussain J.; Hussein, Wisam A.; Naeem, Sarah Mazin; Naeem, Sarah Mazin (Journal of Posthumanism, 2025)
This study investigates the effect of low-dose bisphosphonates on the healing process and functional recovery in patients with pathological bone fractures, conditions that predispose individuals to fractures due to underlying disorders such as osteoporosis or metastatic cancers. Bisphosphonates, traditionally used for their bone-preserving qualities, may enhance fracture healing by inhibiting osteoclast-mediated bone resorption. The primary objectives of this randomized controlled trial were to compare healing time, grip strength, and walking endurance between patients receiving bisphosphonates and those undergoing standard care. A total of 30 patients diagnosed with pathological fractures were randomly assigned to receive either bisphosphonates or standard care. The outcomes revealed that bisphosphonates were associated with a significantly shorter fracture healing time and improved walking endurance. However, grip strength did not show a statistically significant difference between the two groups. Additionally, pain intensity and quality of life were notably better in the bisphosphonate group. The findings suggest that low-dose bisphosphonates may offer significant benefits in accelerating fracture healing and improving functional recovery, particularly in mobility, without negatively impacting grip strength. These results warrant further investigation into the therapeutic potential of bisphosphonates for patients with pathological fractures.